Neural correlates of derived relational responding on tests of stimulus equivalence - Schlund, Michael W; Cataldo, Michael F; Hoehn-Saric, Rudolf (Behavioral and brain functions, 2008)
An essential component of cognition and language involves the formation of new conditional relations between stimuli based upon prior experiences. Results of investigations on transitive inference (TI) highlight a prominent role for the medial temporal lobe in maintaining associative relations among sequentially arranged stimuli (A > B > C > D > E). In this investigation, medial temporal lobe activity was assessed while subjects completed "Stimulus Equivalence" (SE) tests that required deriving conditional relations among stimuli within a class (A identical with B identical with C). Stimuli consisted of six consonant-vowel-consonant triads divided into two classes (A1, B1, C1; A2, B2, C2). A simultaneous matching-to-sample task and differential reinforcement were employed during pretraining to establish the conditional relations A1:B1 and B1:C1 in class 1 and A2:B2 and B2:C2 in class 2. During functional neuroimaging, recombined stimulus pairs were presented and subjects judged (yes/no) whether stimuli were related. SE tests involved presenting three different types of within-class pairs: Symmetrical (B1 A1; C1 B1; B2 A2; C2 B2), and Transitive (A1 C1; A2 C2) and Equivalence (C1 A1; C2 A2) relations separated by a nodal stimulus. Cross-class 'Foils' consisting of unrelated stimuli (e.g., A1 C2) were also presented. Relative to cross-class Foils, Transitive and Equivalence relations requiring inferential judgments elicited bilateral activation in the anterior hippocampus while Symmetrical relations elicited activation in the parahippocampus. Relative to each derived relation, Foils generally elicited bilateral activation in the parahippocampus, as well as in frontal and parietal lobe regions. Activation observed in the hippocampus to nodal-dependent derived conditional relations (Transitive and Equivalence relations) highlights its involvement in maintaining relational structure and flexible memory expression among stimuli within a class (A identical with B identical with C).